A pit in the Mandapa (pillared hall) of Shiva Temple - Temples of India Project Team (Jio Institute, 2024)
In the mandapa (pillared hall) of Shiva Temple (Temple 1), a small pit can be found on the proper left. The actual purpose of the pit is not known, but it is interesting to note because no other temple in this complex reveals a similar kind of structure on the floor.